Short-term growth and biomechanical responses of the temperate seagrass Cymodocea nodosa to CO2 enrichment - de los Santos, Carmen B. (2018)
Seagrasses are often regarded as climate change 'winners' because they exhibit higher rates of photosynthesis, carbon fixation and growth when exposed to increasing levels of ocean acidification. However, questions remain whether such growth enhancement compromises the biomechanical properties of the plants, altering their vulnerability to structural damage and leaf loss. Here, we investigated the short-term (6 wk) effects of decreasing pH by CO2 enrichment on the growth, morphology and leaf-breaking force of the temperate seagrass Cymodocea nodosa. We found that the plant biomass balance under levels of acidification representative of short-term climate change projections (pH 8.04) was positive and led to an increase in leaf abundance in the shoots. However, we also found that plant biomass balance was negative under levels of acidification experienced presently (pH 8.29) and those projected over the long-term (pH 7.82). Leaf morphology (mean leaf length, thickness and width) was invariant across our imposed acidification gradient, although leaves were slightly stronger under [CO2] representative of short-term climate change. Taken together, these findings indicate that a subtle increase in growth and mechanical resistance of C. nodosa is likely to occur following short-to medium-term changes in ocean chemistry, but that these positive effects are unlikely to be maintained over the longer term. Our study emphasises the need to account for the interdependencies between environmental conditions and variations in multiple aspects of the structure and functioning of seagrass communities when considering the likely consequences of climate change.